Analysis Of The Implementation Of Standard Operating Procedures (SOP) In The Administration Division At PT Rezeki Surya Intimakmur (PT RSI) - Abel Armanda Putra; Muhammad Bakr Muhlison (Cita konsultindo, 2024)
This research was conducted alongside the internship program at PT Rezeki Surya Intimakmur (PT RSI) from March 1, 2023, to June 31, 2023. The purpose of this research is to analyze the implementation of Standard Operating Procedures (SOP) at PT RSI. The research focuses on the administrative division, which handles the maintenance project for air conditioners and generators at Starbucks. PT RSI is a contracting company that collaborates with both national and international companies. Therefore, PT RSI must maintain its credibility by consistently adhering to proper SOPs. This research uses the theory from Santosa's book entitled